A STUDY ON BRAND PERCEPTİON İN PURCHASİNG PREFERENCES OF GENERATİONS Y İN THE AVİATİON INDUSTRY (Third Sector Social Economic Review, 2022)
With the increasing importance of air transport today, its share in the market has increased to a great extent. Airline companies should be the reason for preference by making some differences in order to retain their passengers and attract new passengers. In addition, it is important to investigate the Y  generations, which make up the majority of the segment that uses air transport today. The importance of the research is to explain that brand perception makes a difference in the direction of purchasing. The aim of the study is to measure the Y  generation purchasing preferences of the brand perceptions created by the airline companies in Turkey. In the aviation sector, where competition is intense, businesses are looking for some innovations in order to be different. In this, they should develop marketing strategies dominated by dynamism. Brand perception, satisfaction and adoption scales in the literature were used. The universe of the research consists of Y  generation passengers who use air transport in Turkey. Since it is not possible to evaluate all Y  generation passengers using air transport, people over the age of 18 who have used air transport in Turkey at least once before, using the maximum diversity sampling method, constitute the sample of the research. In this context, a sample of 368 people was used in the study. The subject of the research was limited to the airline companies serving in Turkey, and the research was carried out on Y  generation passengers using air transport. While conducting the research, questionnaire application and literature review were deemed sufficient. While creating the literature review section of the research, reports, articles, books and web sites were used
Keywords: Aviation Industry; Generation Y; Brand Perception; Purchasing Intention; Marketing